With Shaking Hands : Aging with Parkinson's Disease in America's Heartland - Solimeo, Samantha (Book collections on Project MUSE., 2009)
Far from celebrity media spotlight, ordinary individuals, many older and less advantaged, suffer the disabling pain of Parkinson's disease (PD), an illness whose progressive symptoms often mimic old age and cause mobility impairment, communication barriers, and social isolation. At the heart of With Shaking Hands is the account of elder Americans in rural Iowa who have been diagnosed with PD. With a focus on the impact of chronic illness on an aging population, Samantha Solimeo combines clear and accessible prose with qualitative and quantitative research to demonstrate how the disease acceler.